Pengaruh Harga dan Online Customer Review Terhadap Keputusan Pembelian Produk Fashion di Marketplace Shopee pada Mahasiswa Universitas Bhinneka PGRI - Sorkhana Dini, Fatkhillah Za'im; Anasrulloh, Muhammad (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of price and online customer reviews on purchasing decisions for fashion products in the Shopee marketplace among students of Bhinneka PGRI University, Tulungagung. This study uses a quantitative approach with a causal associative method. Data were obtained through questionnaires from 100 students of the Economics Education Study Program in semesters 6 and 8. Data were analyzed using multiple linear regression with a t-test to test partial effects, an F-test to test simultaneous effects, and a coefficient of determination to determine the contribution of independent variables to purchasing decisions. The results showed that price had a positive and significant effect on purchasing decisions (t = 8.844; sig. = 0.000), as did online customer reviews (t = 3.206; sig. = 0.002). Simultaneously, price and online customer reviews had a significant effect on purchasing decisions (F = 122.790; sig. = 0.000) with a contribution of 71.1%, while 28.9% was explained by other factors outside the research model. These findings indicate that purchasing decisions for fashion products on Shopee are influenced by price considerations as well as consumer information and experience reflected in online customer reviews